Exploring Students’ Perception in Learning Structure & Written Expression in TOEFL through YouTube Channels in English Literature Students of Pamulang University - Meylinda, Linda (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2024)
This research aims to explore students' views on learning TOEFL through YouTube channels and assess its effectiveness for English Literature majors at Pamulang University. Data were gathered by analyzing responses from 25 second-semester students via a questionnaire. The data were processed through reduction, presentation, and conclusion drawing. The findings indicate that students responded positively to this learning method, with most finding it engaging and beneficial. The use of YouTube channels in TOEFL preparation, particularly for understanding structure and written expression, was found to enhance students' motivation and deepen their comprehension of the material. Therefore, this study supports the use of YouTube channels as an effective tool for improving TOEFL learning at the university level